2009
DOI: 10.1007/s12306-009-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a primary multiloculate muscular cystic hydatidosis

Abstract: Hydatidosis is a zoonosis caused by the ingestion of Echinococcus granulosus eggs, released though the feces, from infected dogs to humans. Primary localization is mostly hepatic and/or pulmonary, whereas muscular involvement is very rare, even more so in muscular striated tissue. This is the report of a case of a primary intramuscular hydatid cyst in a 79-year-old woman who presented with a 3-year history of a painful lump in her proximal medial left thigh. The authors document the exceptional giant dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the tropics, visceral larva migrans (toxocarosis) may manifest as tropical pyomyositis requiring repeated debridement . Hydatid cysts from infestation with Echinococcus may rarely occur in a single muscle as the initial manifestation . Most commonly, liver and lung are affected .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tropics, visceral larva migrans (toxocarosis) may manifest as tropical pyomyositis requiring repeated debridement . Hydatid cysts from infestation with Echinococcus may rarely occur in a single muscle as the initial manifestation . Most commonly, liver and lung are affected .…”
Section: Resultsmentioning
confidence: 99%
“…Hydatid cysts from infestation with Echinococcus may rarely occur in a single muscle as the initial manifestation . Most commonly, liver and lung are affected . Hydatid cysts of the muscle have been occasionally observed in patients with primary muscle disease .…”
Section: Resultsmentioning
confidence: 99%
“…Possible differential diagnoses include lipoma, calcified hematoma, cold abscess or soft tissue tumour. Musculoskeletal echinococcosis should always be suspected in patients originating from endemic regions (1,5,6,14).…”
Section: Discussionmentioning
confidence: 99%
“…Case V was in a 34 year old woman with a 4x3x2 cm HC in the gastrocnemius muscle. Notarnicola et al (2009) reported a case of primary intramuscular HC in a 79 year old woman who presented with a 3 year history of a painful lump in her proximal left thigh. They documented exceptional giant dimensions of the cyst which was not previously reported in a case of striated muscular HD.…”
Section: Introductionmentioning
confidence: 99%